Environment and sustainable development in South Asia - Tripathi, Sudhanshu (2007)
The problem of environmental degradation affecting ecological balance in South Asia has its roots in several factors particularly socio-economic backwardness, lack of popular participation in policy formation and lack of collective effort at national as well as regional level. A corrective to this situation would be proper utilisation of the forum of SAARC and also developing partnership among public, industry and government for achieving sustainable development assuring human well-being. - Reproduced.
Keywords: Environment - South Asia; Sustainable development - South Asia; Environment